Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1126/science.1079354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Surface Curvature

Abstract: Although curvature of biological surfaces has been considered from mathematical and biophysical perspectives, its molecular and developmental basis is unclear. We have studied the cin mutant of Antirrhinum , which has crinkly rather than flat leaves. Leaves of cin display excess growth in marginal regions, resulting in a gradual introduction of negative curvature during development. This reflects a change in the shape and the progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
688
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 676 publications
(727 citation statements)
references
References 22 publications
18
688
0
7
Order By: Relevance
“…Free non-Euclidean thin elastic sheets arise in a variety of physical [1,3,8] and biological [2,11,33] systems. The morphology of these sheets is usually modeled as the equilibrium configurations for an appropriate elastic energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free non-Euclidean thin elastic sheets arise in a variety of physical [1,3,8] and biological [2,11,33] systems. The morphology of these sheets is usually modeled as the equilibrium configurations for an appropriate elastic energy.…”
Section: Discussionmentioning
confidence: 99%
“…The differential growth of thin elastic sheets can generate highly nontrivial configurations such as the multiple generation of waves along the edge of a torn elastic sheet [1] and the wrinkled patterns on leaves [2]. Recently, environmentally responsive gel disks of uniform thickness have been created in the laboratory that mimic this type of growth by differentially shrinking in the radial direction when thermally activated in a hot water bath [3].…”
Section: Introductionmentioning
confidence: 99%
“…In cin mutant of Antirrhinum, the leaf margin is rumpled as a result of the slower arrest of cell divisions at the leaf margins relative to the middle of the leaf, and a comparable phenotype is seen in jaw-D mutation of Arabidopsis [29,30]. In both cases, TCP-domain genes [31] and regulation of their expressions are responsible for the development of flat and curved leaf surface.…”
Section: Wps1 Could Be a Downstream Component In The B Function Durinmentioning
confidence: 99%
“…LA encodes a transcription factor from the TCP family that contains a miR319-binding site [9,73]. Ori et al [19] found that the reduced sensitivity to miR319 resulted in elevated LA expression in very young leaf primordia and accelerated differentiation of leaf margins.…”
Section: Transgenic Analysis In Exploring Mirnas Functionmentioning
confidence: 99%